Catalytic Upgrading of Biomass-Derived γ-Valerolactone to Biofuels and Valuable Chemicals - He, Jian; Wang, Zhongwei; Zhao, Wenfeng; Yang, Tingting; Liu, Yanxiu; Yang, Song (Current Catalysis, 2017)
Background: To alleviate the crisis from depletion in non-renewable fossil reserves, catalytic conversion of the most abundant and renewable lignocellulosic biomass to biofuels and value-added chemicals has received much attention. In this respect, γ-valerolactone (GVL) derived from carbohydrates has gained considerable attention, as it can be further converted to biofuels and value-added chemicals via different catalytic processes such as hydrogenation, ring-opening, decarboxylation, isomerization and oligomerization. This work aims to review the most relevant research in the catalytic upgrading of GVL into fuel additives, biofuels and various valuable chemicals. Focus is also placed on the corresponding reaction pathways and catalytic mechanisms. Methods: We searched peer-reviewed research literatures in Web of Science using focused review questions. In this review, focus was primarily put on the catalytic upgrading of GVL into biofuels and valuable chemicals, such as (i) 2-methyltetrahydrofuran and isooctane, (ii) valeric biofuels and 5-nonanone, (iii) liquid alkenes fuels, #136;iv#137;1,4-pentanediol and aromatic hydrocarbons, and#136;v#137;128;polymers. Meanwhile, the properties of GVL and the recent advances in the production of GVL from biomass and its derivatives were also described in the introduction section of this review. Results: Ninety-two papers were included in the review. A part of papers (i.e., 16) briefly outlined the properties of GVL and its wide range of potential applications. Twenty-seven papers summarized recent advances in the catalytic production of GVL from biomass and its derivatives. The majority of papers (49) described recent advances in catalytic upgrading of GVL into bio-fuels and valuable chemicals. Among them, ten papers depicted the upgrading of GVL to 2-methyltetrahydrofuran and isooctane, sixteen papers illustrated the conversion of GVL to valeric biofuels and 5-nonanone, seven papers described the transformation of GVL into liquid alkenes fuels, seven papers reviewed the catalytic production of 1,4-pentanediol and aromatic hydrocarbons from GVL, and the upgrading of GVL to polymers were described in nine papers. This review not only depicted the upgrading pathways of GVL but also focused on the corresponding catalytic mechanisms. Conclusion: The findings of this review confirm the importance of upgrading of GVL to bio-fuels and valuable chemicals. Meanwhile, the review suggests that designing efficient and multifunctional catalysts is crucial for various routes to upgrade GVL.
Keywords: heterogeneous catalysis